Early response of the human SOST gene to stimulation by 1α, 25-dihydroxyvitamin D3. Issue 164 (November 2016) - Wijenayaka, Asiri R.; Prideaux, Matthew; Yang, Dongqing; Morris, Howard A.; Findlay, David M.; Anderson, Paul H.; Atkins, Gerald J.
Highlights: We examined SOST mRNA and sclerostin protein levels in differentiated SaOS2 cultures. SOST expression was induced by 1, 25D after 3 h at the mRNA level. Sclerostin protein levels increased by 12 h in response to 1, 25D. Abstract: The osteocyte expressed gene SOST encodes sclerostin, a potent negative regulator of bone formation and inducer of bone resorption. We have recently demonstrated that the human SOST gene is positively regulated in response to 1α, 25-dihydroxyvitamin D3 (1, 25D). Responsiveness may be mediated at least in part by a single classical DR3-type vitamin D response element (VDRE). In this study we examined the early responsiveness of the SOST gene to both 1, 25D and to parathyroid hormone (PTH), a known repressor of SOST expression, in SaOS2 cells differentiated to an osteocyte-like stage of cell maturation. Both SOST mRNA levels and sclerostin protein levels increased in these cultures as early as 3 h post-treatment with 1, 25D and declined in response to PTH in the same timeframe. For 1, 25D, the level of induced SOST appeared dependent on the extent, to which the degradative enzyme 1, 25-dihydroxyvitamin D 24-hydroxylase ( CYP24A1 ) was induced. Together with the observed rapid decrease in SOST /sclerostin levels in response to PTH, endocrine regulation of sclerostin production appears to be an important determinant of sclerostin levels. These findings confirm that the human SOST gene and sclerostin expression can be considered to be directly 1, 25D-responsive in osteocytes.